2017
DOI: 10.1515/quageo-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial and Temporal Analysis of Land Use Changes in Two Mountain Valleys: with and without Dam Reservoir (Polish Carpathians)

Abstract: Wiejaczka Ł, olędzki j.R., BucaŁa a., kijoWska-stRugaŁa M. 2017. A spatial and temporal analysis of land use changes in two mountain valleys: with and without dam reservoir (Polish Carpathians). Quaestiones Geographicae 36(1), Bogucki Wydawnictwo Naukowe, Poznań, pp. 129-137, 5 figs, 4 tables.aBstRact: This study analyzed the temporal and spatial changes in land use taking place in two adjacent river valleys, located within the Polish Carpathians. The land use in 1977 and 2009 was presented for selected areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(16 reference statements)
2
8
0
1
Order By: Relevance
“…The water bodies increased significantly during the post-dam construction period, which can be attributed to the increase in the level of the reservoir created by the hydroelectric dam in the BNP, an observation that has been reported by other similar studies elsewhere (Obahoundje et al, 2018; Wiejaczka et al, 2017; Zhao et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The water bodies increased significantly during the post-dam construction period, which can be attributed to the increase in the level of the reservoir created by the hydroelectric dam in the BNP, an observation that has been reported by other similar studies elsewhere (Obahoundje et al, 2018; Wiejaczka et al, 2017; Zhao et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…The grassland decreased its cover from 2010-2020. Other researches (Chalise et al, 2019;Özüpekçe, 2019;Wiejaczka et al, 2017;Xu & Chi, 2019) have reported similar occurrence of post-dam grassland decline in protected areas. Illegal mining, uncontrolled cattle grazing and charcoal production could account for the decline of grassland during this period.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Humans have powerfully influenced changes in every aspect of the landscape (Dale, King, Washington‐Allen, & McCord, ; Feranec, Jaffrain, Soukup, & Hazeu, ; Wiejaczka, Kijowska‐Strugała, Pierwoła, & Nowak, ; Wiejaczka, Olędzki, Bucała‐Hrabia, & Kijowska‐Strugała, ), which historically was conditioned by natural factors such as climate, relief, and soil properties (Bellwood, ; Lambin & Meyfroidt, ). Regardless of the type and duration of human activity in the natural environment, the effects of this impact typically first appear as changes in natural vegetation (Benjamin, Domon, & Bouchard, ; Bucała, Budek, & Kozak, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors that control channels morphology have been recognized. One of the most important of them are channelization, gravel mining [4], [5] and dams construction [6]. Moreover, land use and land cover changes (LULCC) can also lead to a river channels changes [7], [8].…”
Section: Introductionmentioning
confidence: 99%